The histamine analogue clobenpropit modulates IRF7 phosphorylation and interferon production by targeting CXCR4 in systemic lupus erythematosus models - Nassima Bekaddour; Nassima Bekaddour; Nikaïa Smith; Birgit Caspar; Birgit Caspar; Severine Grinberg; Severine Grinberg; Stephane Giorgiutti; Stephane Giorgiutti; Stephane Giorgiutti; Vincent Rodeschini; Stephanie Dupuy; et al. (Frontiers in Immunology, 2024)
IntroductionSystemic lupus erythematosus (SLE) is an autoimmune disease characterized by an overactive immune response, particularly involving excessive production of type I interferons. This overproduction is driven by the phosphorylation of IRF7, a crucial factor in interferon gene activation. Current treatments for SLE are often not very effective and can have serious side effects.MethodsOur study introduces clobenpropit, a histamine analogue, as a potential new therapy targeting the CXCR4 receptor to reduce IRF7 phosphorylation and subsequent interferon production. We employed various laboratory techniques to investigate how clobenpropit interacts with CXCR4 and its effects on immune cells from healthy individuals and SLE patients.ResultsClobenpropit binds effectively to CXCR4, significantly inhibiting IRF7 phosphorylation and reducing interferon production. Additionally, clobenpropit lowered levels of pro-inflammatory cytokines in a mouse model of lupus, demonstrating efficacy comparable to the standard treatment, prednisolone.DiscussionThese results suggest that clobenpropit could be a promising new treatment for SLE, offering a targeted approach with potential advantages over current therapies.